2023
DOI: 10.3389/fpls.2023.1268739
|View full text |Cite
|
Sign up to set email alerts
|

Promising physiological traits associated with nitrogen use efficiency in rice under reduced N application

Bathula Srikanth,
Desiraju Subrahmanyam,
Durbha Sanjeeva Rao
et al.

Abstract: Higher grain yield in high-yielding rice varieties is mostly driven by nitrogen (N) fertilizer applied in abundant amounts leading to increased production cost and environmental pollution. This has fueled the studies on nitrogen use efficiency (NUE) to decrease the N fertilizer application in rice to the possible extent. NUE is a complex physiological trait controlled by multiple genes, but yet to be completely deciphered in rice. With an objective of identifying the promising physiological traits associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 109 publications
0
0
0
Order By: Relevance
“…The yield reduction in the eld for IR64 and N22 was 2.67 and 42.15%, and in our hydroponics study we found a reduction in yield by 8.8 and 54%. Other than yield, we have observed effect of nitrogen stress in most other parameters under study was as reported in other references(Fan et al 2010;Koutroubas et al 2008;Srikanth et al 2023), and hence, we nalized the N-concentration in stress condition as 0.8mM.…”
mentioning
confidence: 61%
“…The yield reduction in the eld for IR64 and N22 was 2.67 and 42.15%, and in our hydroponics study we found a reduction in yield by 8.8 and 54%. Other than yield, we have observed effect of nitrogen stress in most other parameters under study was as reported in other references(Fan et al 2010;Koutroubas et al 2008;Srikanth et al 2023), and hence, we nalized the N-concentration in stress condition as 0.8mM.…”
mentioning
confidence: 61%